FORMALDEHİT'E MARUZ BIRAKILAN SIÇANLARIN BÖBREK DOKULARINDA SALBUTAMOL'ÜN, PODOCALYXİN VE PENTRAXİN 3 ÜZERİNE ETKİLERİNİN İNCELENMESİ - SERVİ, NAZİFE (Fırat Üniveristesi, 2026)
Formaldehit (FA), dokularda toksisite oluşturmakta, oksidatif strese neden olmakta ve antioksidan düzeylerini düşürmektedir. Salbutamol ise oksidan maruziyetinin neden olduğu hasarı iyileştirmektedir. Bu çalışmada amacımız; FA maruziyetinin oluşturduğu hasarı kan ve böbrekte enzim bağlı immünosorbent test (ELISA) ile ve böbrek dokusunda ise histopatolojik olarak incelemek; böbrek üzerine toksitisesi bilinen FA'nın etkilerine karşı salbutamolün etkilerini aynı yöntemlerle değerlendirmek; ayrıca FA ve salbotamolün podocalyxin (PODXL) ve pentraxin 3 (PTX3) seviyeleri üzerindeki değişimini incelemektir. Çalışmada 10-12 haftalık 28 adet Sprague-Dawley cinsi erkek sıçan kullanıldı. Kan ve böbrek süpernatantlarında total antioksidan (TAS), total oksidan (TOS), PTX3 ve PODXL seviyeleri tayin edildi. Beraberinde böbrek dokularında immünohistokimyasal yöntemlerle PTX3 ve PODXL immünreaktiviteleri belirlendi. FA maruziyeti, deney hayvanlarının serum ve böbreklerinde TAS düzeylerinde azalmaya, TOS düzeylerinde ise yükselmeye neden oldu. Buna ek olarak PTX3 ve PODXL düzeylerinde düşüşe yol açtığı gözlendi. Antioksidan olarak verilen salbutamol serum ve böbrekte TAS düzeylerinde artma, TOS düzeylerinde azalmaya yol açtı. FA'nın yanına salbutamolü eklediğimiz zaman PTX3 ve PODXL düzeyleri arttı. Sonuç olarak; salbutamol, FA maruziyetinin neden olduğu oksidatif hasarı baskılamakta ve oluşan histopatolojik bozulmaları geri çevirmektedir.

Formaldehyde (FA) induces toxicity in tissues, causes oxidative stress, and reduces antioxidant levels. Salbutamol, on the other hand, has been shown to ameliorate damage caused by oxidant exposure. The aim of this study was to evaluate FA-induced damage in blood and kidney tissues using enzyme-linked immunosorbent assay (ELISA) and to examine histopathological alterations in kidney tissue; to assess the effects of salbutamol against the known nephrotoxic effects of FA using the same methods; and to investigate changes in podocalyxin (PODXL) and pentraxin-3 (PTX3) levels associated with FA and salbutamol administration. In this study, twenty-eight male Sprague–Dawley rats aged 10–12 weeks were used. Total antioxidant status (TAS), total oxidant status (TOS), PTX3, and PODXL levels were determined in serum and kidney supernatants. In addition, PTX3 and PODXL immunoreactivities in kidney tissues were evaluated using immunohistochemical methods.FA exposure resulted in decreased TAS levels and increased TOS levels in the serum and kidney tissues of the experimental animals. Moreover, reductions in PTX3 and PODXL levels were observed. Administration of salbutamol as an antioxidant led to increased TAS levels and decreased TOS levels in both serum and kidney tissues. When salbutamol was administered concomitantly with FA, PTX3 and PODXL levels were found to increase.In conclusion, salbutamol suppresses oxidative damage induced by FA exposure and reverses the associated histopathological alterations.
Evaluation of the effects of salbutamol on podocalyxin and pentraxin 3 levels in renal tissues of formaldehyde-exposed rats
Keywords: Anatomi